Spatial regulation of protein A in Staphylococcus aureus. Issue 2 (14th June 2021) - Zhang, Ran; Shebes, Mac A.; Kho, Kelvin; Scaffidi, Salvatore J.; Meredith, Timothy C.; Yu, Wenqi
Abstract: Surface proteins of Staphylococcus aureus play vital roles in bacterial physiology and pathogenesis. Recent work suggests that surface proteins are spatially regulated by a YSIRK/GXXS signal peptide that promotes cross‐wall targeting at the mid‐cell, though the mechanisms remain unclear. We previously showed that protein A (SpA), a YSIRK/GXXS protein and key staphylococcal virulence factor, mis‐localizes in a ltaS mutant deficient in lipoteichoic acid (LTA) production. Here, we identified that SpA contains another cross‐wall targeting signal, the LysM domain, which, in addition to the YSIRK/GXXS signal peptide, significantly enhances SpA cross‐wall targeting. We show that LTA synthesis, but not LtaS, is required for SpA septal anchoring and cross‐wall deposition. Interestingly, LTA is predominantly found at the peripheral cell membrane and is diminished at the septum of dividing staphylococcal cells, suggesting a restriction mechanism for SpA septal localization. Finally, we show that D‐alanylation of LTA abolishes SpA cross‐wall deposition by disrupting SpA distribution in the peptidoglycan layer without altering SpA septal anchoring. Our study reveals that multiple factors contribute to the spatial regulation and cross‐wall targeting of SpA via different mechanisms, which coordinately ensures efficient incorporation of surface proteins into the growing peptidoglycan during the cell cycle. Abstract : Staphylococcal Protein A (SpA) is a cell wall anchored surface protein and a key virulence factor. During its biogenesis, it is targeted to the division septum by its N‐terminal YSIRK/G‐S signal peptide and anchored to the cross‐wall between the two daughter cells. Here, we report that multiple factors spatially regulate SpA biogenesis: the LysMSpA domain enhances SpA cross‐wall targeting, LtaS‐mediated lipoteichoic acid (LTA) synthesis regulates SpA septal localization, and LTA D‐alanylation modulates SpA cross‐wall deposition.